Lanthanide(iii) morpholine 4-dithiocarbamate complexes: Pr(iii) derivative shows first example of polymeric lanthanide(iii) dithiocarbamate1. Issue 76 (19th August 2015) - Mahato, Mamata; Jana, Partha P.; Harms, Klaus; Nayek, Hari Pada
<x xml:space="preserve">Abstract</x> Polymeric and discrete Ln(iii) morpholine 4-dithiocarbamate complexes [Ln(Phen)(Mph-Dtc)3]x·CH2Cl2 [Ln = Pr (1), Nd (2) and Eu (3); Mph-Dtc = morpholine 4-dithiocarbamate; x = 2 (1) or 1 (2, 3)] have been synthesized and characterized.